2011
DOI: 10.1186/bcr3068
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of adjuvant chemotherapy for patients with triple-negative breast cancer at Stage II: usefulness of prognostic markers E-cadherin and Ki67

Abstract: IntroductionTriple-negative breast cancer (TNBC), which is characterized by negativity for estrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 (HER2), is a high risk breast cancer that lacks specific targets for treatment selection. Chemotherapy is, therefore, the primary systemic modality used in the treatment of this disease, but reliable parameters to predict the chemosensitivity of TNBC have not been clinically available.MethodsA total of 190 TNBC patients who had undergon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 47 publications
(48 reference statements)
3
55
0
Order By: Relevance
“…TNBC has proven to be remarkably heterogeneous with various prognoses stratified by clinical, pathological, genetic factors, and treatment modalities [1][5]. For example, stage II TNBC cases treated with adjuvant chemotherapy would have a better prognosis than those receiving no chemotherapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…TNBC has proven to be remarkably heterogeneous with various prognoses stratified by clinical, pathological, genetic factors, and treatment modalities [1][5]. For example, stage II TNBC cases treated with adjuvant chemotherapy would have a better prognosis than those receiving no chemotherapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some publications emphasize that adding chemotherapy to endocrine therapy is a recommended treatment in this population of patients [15]. Different cutoff values of Ki-67 LI have been proposed for the indication of chemotherapy for these patients [9,12,16,17,18]. Owing to the relevance of this factor in recommending the addition of chemotherapy, the reproducibility of Ki-67 LI evaluation is highly important.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-Ki-67 antibody labeling index (LI, percentage of nuclear antigen-positive cells) has been proposed as a prognostic and predictive marker for breast cancer, especially for estrogen receptor (ER)-positive, HER2-negative early breast carcinoma [1,6,7,8]. Different studies have demonstrated that a high Ki-67 LI indicates an increased risk of recurrence [7,9,10], metastasis [7,8,9,11,12,13,14,15] and faster progression of the disease. Some publications emphasize that adding chemotherapy to endocrine therapy is a recommended treatment in this population of patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ki67 expressed significantly in a higher stage of TN tumors and high lymph node metastasis [36]. They also suggested that the patients having higher expression of ki67 showed a significantly worse overall survival (OS) time.…”
Section: Ki67mentioning
confidence: 97%